(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Chickenpox (lat. Varicella) is the general name of a number of viral infections. It is manifested by the appearance of red rashes and granules all over the body. The disease can be observed repeatedly in very rare cases, usually people get this disease once in their lifetime.